Relationship between the features of Information System (IS) quality and job satisfaction among staff at Risda , Melaka / Mohammad Hafiz Mohmad Zamary - Mohmad Zamary, Mohammad Hafiz (Faculty of Business and Management, 2013)
RISDA are one of the Federal Statutory Bodies under the Ministry of Rural and Regional Development. The date of January I, 1973 that RISDA was established under the authorities endorsed by Parliament.RISDA was established as the Government sees the importance of new policies and strategies for the development of the smallholder sector. The RISDA establishment is specifically developed to guide the progress, both social and economic development of the smallholder sector. RISDA takes responsibility in the process of developing new attitudes and conceptualizations based on the current demands of the market. Smallholders are exposed to the complete application of research and technical advancements in rubber cultivation and processing. Thus, RISDA cooperates with MARDEC in creating an efficient marketing system for the smallholder. Hence, the elements of modernization are clear to enable all smallholders in utilizing modem practices to increase the quality of rubber production quality to earn higher returns. This will malce the nation's natural rubber industry become stronger and much more stable. RISDA will give its full cooperation to all related government agencies. Undoubtedly, RISDA will playa very important role in the execution of the "Dasar Ekonomi Bam (DEB)", particularly in the restructuring of society. This research will look into how the Information System will affect the effectiveness of RISDA and their employees. This research will also investigate whether the Information System have any implications towards the effectiveness of RISDA. Therefore, this study proposes to investigate the relationship between the features of Information System (IS) quality and job satisfaction among staff at RISDA.